Sinergi Pendidikan Islam dan Digital Untuk Generasi Muslim Unggul Global Mandiri - Aisyah Rahayu; Fedya Jelila; Gusmaneli (CV. ITTC INDONESIA, 2025)
Islamic education plays a central role in producing individuals who are spiritually, intellectually, and socially harmonious based on the Qur’an and Sunnah. This study aims to examine the optimization of the Islamic education ecosystem through the synergy of the prenatal environment, family, school, and community, as well as the use of digital innovation to face the challenges of globalization. Using qualitative descriptive methods and an interdisciplinary approach, this study analyzes the characteristics, roles, and challenges of the Islamic education environment. The results show that collaboration between environments supported by technology, such as Qur’an learning applications and STEAM-based curriculum, can improve the effectiveness of education. Challenges such as secularism and the influence of social media can be overcome by integrating 21st-century skills, such as digital literacy and critical thinking, without sacrificing Islamic values. Recommendations include prenatal training, strengthening the role of the family, increasing teacher capacity, activating religious communities, and developing digital platforms. This study confirms that adaptive Islamic education can produce a generation of Muslims who are superior, competitive, and relevant in the global arena.